Success Strategies from Women in STEM. (October 2015) - Unknown
Abstract : The domains of science, technology, engineering and mathematics (STEM) have often been difficult career environments for women. And while great strides have been made in realising the previously untapped potential of this half of the population, one area seems to remain a pointlessly male preserve.